Soigner les malades au xve siècle. L’exemple de la fouille de l’hôtel-Dieu de Valenciennes (Nord) - David Delassus; Marie Derreumaux; Dominique Frere; Marie Huin; Hélène Poirier; Tarek Oueslati; Coralie Favero; Arnaud Tixador; Maxime Rageot; Delphine Barbier-Pain; Matthieu Deltombe; Patrice Korpiun; et al. (Archéologie Médiévale, 2023)
Abstract: The Hôtel-Dieu in Valenciennes was excavated in 2016 by the municipal archaeological service. This excavation was a unique opportunity to record the medieval state of the hospital founded in 1430, only known beforehand through written and iconographical sources. The excavation mainly uncovered the western part of the main building. The construction analysis revealed that the sick ward and the chapel didn’t originally occupy the whole building, as the newly uncovered western part housed a semi-excavated space, taking a third of the building. Other arrangements of that same building (water tank, cave) show a will to facilitate the work of nurses by accommodating the requirements of the spiritual as well as the physical aspects of healing. The results must have been found efficient by contemporaries, as it later influenced the construction of the large building of the hospices in Beaune. Last, the excavation of two closed spaces gave various information about the material environment of the sick and their healers, as well as other aspects of healing: food, hygiene, medicine. Two glass sprinklers discovered showed the influence of the Arabic world on the equipment of the hospital in the 15th c.